2023
DOI: 10.1111/pai.13977
|View full text |Cite|
|
Sign up to set email alerts
|

“Frequency of fatal and recurrent anaphylaxis due to COW'S milk: A systematic review and meta‐analysis of observational studies”

Abstract: Cow's milk allergy (CMA) is one of the most common food allergies in infants and young children. Immune reactions in CMA are categorized as immunoglobulin E (IgE)-mediated, non-IgE-mediated, and mixed (IgE combined with non-IgE). CMA can result in anaphylactic reactions. 1 As in other food allergies, anaphylaxis caused by cow's milk is a potentially life-threatening allergic reaction, and some patients experience recurrences even when CMA is identified in the initial reaction.Studies performed in diverse popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…
Pérez-Codesido et al have performed a systematic review and meta-analysis aiming to assess the frequency of recurrent and fatal anaphylaxis due to cow milk allergy in children. 1 Anaphylaxis is a potentially life-threatening event, and cow milk is one of the most frequent causes of food anaphylaxis in children. 2,3 However, as Pérez-Codesido et al have shown, the epidemiology and impact of cow milk anaphylaxis remain insufficiently studied.
…”
mentioning
confidence: 99%
“…
Pérez-Codesido et al have performed a systematic review and meta-analysis aiming to assess the frequency of recurrent and fatal anaphylaxis due to cow milk allergy in children. 1 Anaphylaxis is a potentially life-threatening event, and cow milk is one of the most frequent causes of food anaphylaxis in children. 2,3 However, as Pérez-Codesido et al have shown, the epidemiology and impact of cow milk anaphylaxis remain insufficiently studied.
…”
mentioning
confidence: 99%